Artificial insemination of alpacas with refrigerated semen and the inclusion of two types of egg yolk - García V., Wilber (2017)
The aim of this study was to evaluate the effect of fresh (YHF) and powder (YHP) egg yolk on the motility, viability, functional integrity of the plasma membrane (HOST) and pregnancy rate after insemination using fresh and chilled semen. Thirty ejaculates of five alpacas were collected by the post-copulation method during the months of January to March. Ejaculates were diluted in Tris-glucose plus glycerol to a final concentration of 5%, and the two types of egg yolk were added at a final concentration of 20%. Diluted semen was separated into aliquots and maintained at 15 °C for 8 h and 5 °C for 24 h, where 180 alpacas were inseminated. Motility, viability and sperm HOST value stored at 15 and 5 °C were not affected by the type of egg yolk. Similarly, pregnancy rates were rather similar when inseminated with fresh semen (50.0 and 46.7%), or kept at 15 °C (43.3 and 40%) or 5 °C (33.3 and 30.0%) for YHF and YHP respectively. Pregnancy rate was higher in females inseminated with fresh semen (48.4%) and lower with chilled semen (31.7%) (p<0.05). The results suggested that egg yolk powder can be satisfactorily used as substitute to fresh egg yolk in extenders in fresh and chilled alpaca semen.